Managing technological innovation - Ettlie, John E. (New York ; Chichester, [England] : John Wiley and Sons, 2000)
This book is about: Planning innovation; New products, new processes; managing future technologies; ...
Keywords: Management; Innovation; Technological innovations -- Management; Research, Industrial -- Management